The Effect Of Service Quality And Customer Satisfaction On Customer Loyalty In Coffee Shop - Saputra, Radiansyah Harry; Mariam, Siti; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to explore the relationship between atmosphere, employee attitudes, service quality, coffee quality, and customer satisfaction on customer loyalty in coffee shops. The research method used is quantitative with a descriptive approach. Data collection using a survey and distributed via a google form barcode with a questionnaire, a data analysis method using Structural Equation Modeling (SEM). The research findings show that atmosphere, employee attitudes, and coffee quality have a significant effect on customer satisfaction, while service quality does not show a significant impact. Customer satisfaction, in turn, has a positive effect on customer loyalty. This study emphasizes the importance of a pleasant atmosphere, positive employee attitudes, and high coffee quality in increasing customer satisfaction and loyalty. These findings provide valuable insights for coffee shop managers in designing strategies to improve customer experience and ensure their loyalty. Keywords: Atmosphere, Employee Attitude, Service Quality, Coffee Quality, Customer Satisfaction, Customer Loyalty.